The cutaneous manifistation of Lyme Borreliosis: primary borrelial lymphocytoma and surrounding secondary erythema chronicum migrans - E. V. Sokolovskiy; T. A. Gorislavskaia; G. N. Mikheev (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The authors describe a rare clinical observation of the cutaneous manifistation of Lyme Borreliosis: primary borrelial lymphocytoma and surrounding secondary erythema chronicum migrans. The review of clinical features, histology, is also present.